Konseling Kelompok Dengan Pendekatan Person Centered Therapy dalam Membantu Trauma Pada Korban Kekerasan Seksual - Nurul Aprilia Fitra; Yeni Karneli; Netrawati (Jurnal Ilmu Pendidikan dan Sosial, 2023)
The rise of sexual violence in Indonesia has caused lasting trauma to victims, both physically and verbally, so this is quite a worrying concern, with this endless phenomenon occurring. A group counseling is held which can help victims resolve the trauma. Based on cases that occurred in Indonesia, it was found that sexual violence occurred in children who were in the school environment. Factors that influence the occurrence of sexual violence are the many perpetrators who are people around the victim and even people who are known to the victim so that sexual violence usually occurs anywhere. Furthermore, the factors that influence the emergence of sexual violence are because children are considered sterile so that children are vulnerable to becoming victims of sexual violence because this causes trauma to the victim because of the incident that happened to the victim. Counseling for victims of sexual violence is the first time the counselor conducts counseling using a Person-Centered Therapy approach so that victims get better and can carry out their normal activities and live their lives.